Public Political Participation at Simultaneous Parliamentary and Presidential Elections, Indonesia - Ratna Kustiah; Mahyuni Mahyuni; Samahuddin Muharram (Asean Study Center Lambung Mangkurat University, 2022)
One of the most important parts of an election process is the participation of the community. The purpose of this study is to analyze the level of community participation that did not reach the national target in the 2019 simultaneous general election in Tanah Bumbu district of South Kalimantan province. Public political participation in the general election of members of the Regency / City DPRD in Tanah Bumbu Regency did not reach the national target because the public did not understand the importance of the election by preferring to carry out their economic activities rather than attending invitations to polling stations. The behavior of voters with profit and loss considerations has a great effect on the absence. The next stage requires socialization carried out by candidates from competing parties regarding their vision and mission in building the region.